Explicación paso a paso:
[tex]2x + y = 6 \\ x - 3y = - 4 \\ 2x + y = 6 (3)\\ x - 3y = - 4(1) \\ 6x + 3y = 18 \\ x - 3y = - 4 \\ 7x = 14 \\ x = \frac{14}{7} = 2 \\ x - 3y = - 4 \\ 2 - 3y = - 4 \\ - 3y = - 4 - 2 \\ - 3y = - 6 \\ y = \frac{ - 6}{ - 3} = 2[/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Explicación paso a paso:
[tex]2x + y = 6 \\ x - 3y = - 4 \\ 2x + y = 6 (3)\\ x - 3y = - 4(1) \\ 6x + 3y = 18 \\ x - 3y = - 4 \\ 7x = 14 \\ x = \frac{14}{7} = 2 \\ x - 3y = - 4 \\ 2 - 3y = - 4 \\ - 3y = - 4 - 2 \\ - 3y = - 6 \\ y = \frac{ - 6}{ - 3} = 2[/tex]